Response of Jasmine rice to different levels of irrigation and organic fertilization under SRI cultivation method - Abood Waheed Abood Al-Esawi (Kufa Journal for Agricultural Sciences)
Maintaining a certain level of rice production must coincide with maintaining soil fertility, reducing pollution to the environment, and reducing water consumption. A field experiment was carried out during the 2020 summer growing season in a spot of Al-Issa county-Abbasiya district in the province of Najaf, in order to study the effect of different levels of irrigation and organic fertilizers on the growth, yield and components of the local rice variety Jasmine. The experimental plants were planted on June 17, according to the rice intensification system (SRI) method, by seedling method, at distances of 25 cm between seedlings and lines, with one seedling in the hole. Weeds were removed by hand three times. It was designed as a factorial experiment using a randomized complete block design (RCBD) with three replicates, where the irrigation levels (daily, 3 or 7 days irrigation intervals) as the main factor, while the organic fertilizers at two levels (10 and 5 ton.hˉ¹) were the secondary factor. The results showed that irrigation at 3 days intervals in clay soil mixed with the use of 10 ton.h-1 of organic fertilizers in SRI gave the highest rates of growth characteristics and yield components of Jasmine rice. In the case of irrigation and soil conditions in the study site, SRI is recommended to reduce water consumption and maintain an acceptable level of soil fertility, taking into account maintaining a level of production.